1994
DOI: 10.1073/pnas.91.20.9593
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prosaposin as a neurotrophic factor.

Abstract: Prosaposin was identified as a neurotrophic factor stimulating neurite outgrowth in murine neuroblastoma (NS20Y) cells and choline acetyltranferase (ChAT) activity in human neuroblastoma (SK-N-MC) cells. The four naturally occurring saposs, which are derived by proteolytic processing of prosaposin, were tested for activity. Saposin C was found to be active, whereas saposns A, B, and D were inactive as neurotrophic factors. Dose-response curves demonstrated that nanomolar concentrations of prosaposin and sapos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
171
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(182 citation statements)
references
References 24 publications
7
171
0
Order By: Relevance
“…The molecular mechanisms underlying this neuroprotective effect of 18MP is not fully understood. However, it has been suggested that the high-affinity prosaposin receptor is present on the surface of neuroblastoma cells (O'Brien et al, 1994). Prosaposin at extracellular concentrations greater than 1 ng/mL induces a mitogen-activated protein kinase phosphorylation in PC12 cells (Campana et al, 1996).…”
Section: F Morita Et Al 1300mentioning
confidence: 99%
“…The molecular mechanisms underlying this neuroprotective effect of 18MP is not fully understood. However, it has been suggested that the high-affinity prosaposin receptor is present on the surface of neuroblastoma cells (O'Brien et al, 1994). Prosaposin at extracellular concentrations greater than 1 ng/mL induces a mitogen-activated protein kinase phosphorylation in PC12 cells (Campana et al, 1996).…”
Section: F Morita Et Al 1300mentioning
confidence: 99%
“…However, this disease phenotype appears also, when functional sap-B is absent. 1 A neurotrophic function of the precursor prosaposin protein itself has been elucidated, 7,8 and a role in ganglioside binding and transport has been hypothesized. 9 Recently, the structure of a saposin-like protein, porcine NK-lysin, representative of a family of sequence related proteins sharing a possible common fold, has been determined, comprising five amphipathic α-helices, one at the centre, the others at the two opposite sides, folded into a single globular domain with three disulphide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Neurotrophic activities of SAPLIPs, e.g., prosaposin, saposin C, and a peptide derived from them have been reported in vitro (O'Brien et al, 1994(O'Brien et al, , 1995 and in vivo (Kotani et al, 1996;Liu et al, 2001), suggesting that the neurotrophic activity may reside in the N-terminal domain of CDNF and MANF (Parkash et al, 2009). It is also possible that the neurotrophic activities and cytoprotection against ER stress are mediated by the same structural motif.…”
Section: Receptor Is Unknownmentioning
confidence: 99%